2011
DOI: 10.1369/0022155411423274
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking Potential Intracellular Roles For Dysferlin through Improved Immunolabeling Methods

Abstract: Mutations in the DYSF gene that severely reduce the levels of the protein dysferlin are implicated in muscle-wasting syndromes known as dysferlinopathies. Although studies of its function in skeletal muscle have focused on its potential role in repairing the plasma membrane, dysferlin has also been found, albeit inconsistently, in the sarcoplasm of muscle fibers. The aim of this article is to study the localization of dysferlin in skeletal muscle through optimized immunolabeling methods. We studied the localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 26 publications
4
29
0
Order By: Relevance
“…Dysferlin was also found to coimmunoprecipitate with DHPR from developing myotubes and was hypothesized to be important for the development of the t-tubule (11,15). Other studies found dysferlin at the level of the A-I junction of stretched muscle (14), and we previously localized dysferlin to that region in mature muscle (10). Our current data (cf.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Dysferlin was also found to coimmunoprecipitate with DHPR from developing myotubes and was hypothesized to be important for the development of the t-tubule (11,15). Other studies found dysferlin at the level of the A-I junction of stretched muscle (14), and we previously localized dysferlin to that region in mature muscle (10). Our current data (cf.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, we demonstrated the localization of dysferlin at the A-I junction in mature muscle fibers (10). These results agree with earlier reports associating dysferlin with the dihydropyridine receptor (DHPR, L-type Ca 2+ channel), Ahnak, caveolin 3, and several other proteins involved in Ca 2+ -based signaling and the function of transverse (t-) tubules (11)(12)(13)(14).…”
supporting
confidence: 92%
See 3 more Smart Citations